The contribution of internet use in personal networks of support for long-term condition self-management. (September 2019) - Allen, Chris; Vassilev, Ivaylo; Lin, Sharon Xiaowen; Culliford, David; Rogers, Anne
Objectives: To describe the individual and network characteristics of the personal communities of people using the internet and the role of offline support, network resources and community participation in using the internet for condition management. Methods: Secondary analysis of survey data using logistic regression analysis to determine the factors associated with differential internet use for condition management. This study involved 300 participants from 19 primary care providers in Manchester in 2010 and 2011. Results: Using the internet is associated with age, deprivation, education and having access to a personal network member who understands how to fix computer problems. Those using the internet for condition management received more offline emotional work. No associations were found between using the internet for health and other types of offline support. Those using the internet for support reported lower levels of happiness. Conclusion: Network processes and engagement shape online contact and use of resources for condition management. Those with access to personal networks who provide emotional work are likely to make use of online resources during non-crisis situations, suggesting that these resources act as an extension of offline network support. Those with greater levels of unhappiness may more frequently look to the internet for support.